Answer:
A. A translation right 2 units:
We know that given f(x), the function g(x) = f(x+m), is the same function f(x) but shifted m units to the left. In that sense, a translation right 2 units would be:
g(x) = f(x-2).
B. A translation left 2 units:
We know that given f(x), the function g(x) = f(x+m), is the same function f(x) but shifted m units to the left. In that sense, a translation left 2 units would be:
g(x) = f(x+2).
C. A translation up 2 units:
We know that given f(x), the function g(x) = f(x) + m, is the same function f(x) but shifted m units up. In that sense, a translation up 2 units would be:
g(x) = f(x) + 2
D. A translation down 2 units:
We know that given f(x), the function g(x) = f(x) + m, is the same function f(x) but shifted m units up. In that sense, a translation down 2 units would be:
g(x) = f(x) - 2